Interaksi Sosial Pada Remaja Yang Kecanduan Game Online - luqman hadi; fita qori' fatmala (At-Tarbiyat, 2019)
Currently online games are in great demand by teenagers. Thi is a big concern for educators ang researchers about the impact of online games on teenagers. This article will discuss the impact of online game addiction on adolescent social interactions. Most teenagers today prefer playing games rather than interacting with people around them that cause their interactions to be disrupted. The purpose of this study was to describe and explain in detail how social interactions in adolescents who are addicted to online games. This type of research is field research using a qualitative approach. Methods of collecting data using the method of observation and interviews. From the research found the effect that can be obtained from a teenager who is addicted to online games that is more like being alone, does not follow the organization, and does not gather with people around it. How to deal with the problem of teenagers who are addicted to online games, namely with the advice of parents and also educational institutions about the importance of interacting with people around. Keywords : game online, addiction, social interaction